Hawk eaudiobook - Loveling, Daphne (Lords of Carnage MC, 2018)
HAWK I lost everything years ago. My brother. My family. Everything that ever meant anything to me. Now the Lords of Carnage are my life. Anything I need, the club provides. Anything else is unimportant. At least, that's what I tell myself until I meet Samantha Jennings. She stirs something inside me I haven't felt for years. Back when I had hope. Back when I thought life would give you what you asked for if you wanted it bad enough. Wanting is dangerous. I've learned that lesson. But when I look in those deep brown eyes, I want Samantha. I want to possess every inch of her body—to hear her call my name when she loses herself in pleasure. If I was smart, I'd push her the hell away. Do anything to make her hate me. But I know I won't. I'll never stop until I have her. Even if it destroys us both. SAMANTHA I first saw Hawk McCullough from behind the safety of a camera lens. I try to be invisible when I'm working to capture a moment in a photo. But the way Hawk's eyes locked onto mine, like the lens wasn't even there—I was exposed. They burned into me. Possessing me. Claiming me as his. I can tell from the look in his eyes he's damaged. Ruthless. A predator. I should run far away from him. But I know it's too late. I'm already his prey. Contains mature themes.